Analysis of Factors Affecting Accounting Information Users in UMKM in Lamongan District - Supriyanto, Adi; Fibriyanti, Yenni Vera (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the effect of the owner's education level, business age, and business turnover on the use of accounting information in Micro, Small, and Medium Enterprises (MSMEs) in Lamongan Regency. This study has high urgency because the level of accounting information adoption among MSMEs in Lamongan is still relatively low, whereas proper accounting practices are crucial for business sustainability and development.Unlike previous studies that mostly examined only one or two variables, this research comprehensively investigates three main factors simultaneously to provide a deeper understanding of accounting information usage behavior within the MSME context. This study employs a quantitative approach with an explanatory research design. Primary data were obtained through distributing questionnaires to MSME actors in Lamongan Regency, which served as the population of this study. Out of a total population of 72,924 business units, 100 respondents were selected using a simple random sampling technique. The data were analyzed using multiple linear regression tests.The results indicate that the owner’s education level, business age, and business turnover have a significant effect on the use of accounting information partially. In addition, these three variables also have a significant effect simultaneously. This finding provides new empirical evidence in the context of MSMEs in Lamongan and offers practical implications for local government in designing accounting literacy programs and MSME assistance strategies to enhance business sustainability.